Provenance of upper Triassic sandstone, southwest Iberia (Alentejo and Algarve basins): tracing variability in the sources - Pereira, M. F. (2017)
Laser ablation ICP-MS U–Pb analyses have been conducted on detrital zircon of Upper Triassic sandstone from the Alentejo and Algarve basins in southwest Iberia. The predominance of Neoproterozoic, Devonian, Paleoproterozoic and Carboniferous detrital zircon ages confirms previous studies that indicate the locus of the sediment source of the late Triassic Alentejo Basin in the pre-Mesozoic basement of the South Portuguese and Ossa-Morena zones. Suitable sources for the Upper Triassic Algarve sandstone are the Upper Devonian–Lower Carboniferous of the South Portuguese Zone (Phyllite–Quartzite and Tercenas formations) and the Meguma Terrane (present-day in Nova Scotia). Spatial variations of the sediment sources of both Upper Triassic basins suggest a more complex history of drainage than previously documented involving other source rocks located outside present-day Iberia. The two Triassic basins were isolated from each other with the detrital transport being controlled by two independent drainage systems. This study is important for the reconstruction of the late Triassic paleogeography in a place where, later, the opening of the Central Atlantic Ocean took place separating Europe from North America.